Announcements (Journal of Financial and Quantitative Analysis, 1977)
20-23. Western Finance Association sessions will be at the Quality Inn. The seventeen sessions include cocurrent sessions with empirical and theoretical papers from the major areas of financial research plus two sessions devoted to aspects of the teaching of finance. Three featured sessions are: